Retrato das potencialidades no turismo rural de um município do noroeste do estado do Rio Grande do Sul - Quadros, Letícia Schettert Fortes de (2024)
The rural world has undergone countless transformations that have contributed to its development not being essentially linked to agricultural use. Considering this fact, rural tourism appears to be an alternative for overcoming difficulties and taking advantage of opportunities in rural areas. The main objective of this study was to understand the potential of rural tourism in a municipality in the northwest of the state of Rio Grande do Sul, Palmeira das Missões, from the perspective of rural development. The methodological approach consisted of a case study comprising a first phase, which analyzed documents on tourism in Palmeira das Missões, which pointed to some local attractions with rural tourism possibilities. A second phase involved interviews with some tourism-related organizations, such as Emater-RS/Ascar, the Municipal Tourism Council and the Secretariat of Culture and Tourism of Palmeira das Missões/RS, with the intention of uncovering in-depth information for the research. And finally, a third phase of direct observation and field research on ten rural properties, with open-ended interviews with the owners or people responsible for each of the potentialities. By using the triangulation strategy, converging lines of investigation were sought based on the different sources of evidence. The main conclusion of the research is that the municipality of Palmeira das Missões, RS has potential for rural tourism, as a result of the strategic resources linked to the six tourism dimensions analyzed in this research, which are Culture and Local Characteristics, Natural Dimension, Productive Activities, Gastronomic Dimension, Private/Public Infrastructure and Non-Agricultural Activities. The research also revealed some obstacles that hinder the development of rural tourism in the municipality, such as the precariousness of both public and private infrastructure, the lack of a culture of cooperation between those responsible for the properties and the lack of tourism training.